A lei aplicável aos efeitos atuais dos contratos celebrados antes da vigência do novo Código Civil - Caldas, Rodrigo de Oliveira (2009)
This paper performs a detailed study of a precise rule that presides the passage from the 1916 Civil Code regime, that was valid for almost ninety years, to the 2002 Civil Code regime, valid from january 2003 on. The changing of a Civil Code brings significant consequences for the Law. In fact, the Civil Code was called once Everymen s Constitution (a clearly inadequate expression), since his norms regulate several affairs set every single day. It is not irrelevant so this event, which implies that all facts that take place after the advent of the new order will be placed under its rules. Nevertheless, according to the 5th Article, XXXVI, of Brazilian Constitution, ex post facto laws are prohibited in subject of acquired rights, perfect juridicly acts and res judicata. On the other hand, the 2.035th Article of 2002 Civil Code (10.406/2002 Act) determines that the effects of the contracts celebrated when the 1916 Civil Code was still valid will be ruled by the new order. It is necessary, then, to carefully examine the compatibility between the 2.035th Article of 2002 Civil Code (on which it concerns specifically the effects of the contracts signed before his existence) and the 5th Article, XXXVI of Brazilian Constitution. In conclusion, it can be said that, considered the acquired rights theory, which brasilian Law embraces, as well as the opinions of the brasilian Supreme Court about this particular issue, the 2.035th Article of 2002 Civil Code (10.406/2002 Act) is partialy unconstittucional